Pembangunan pembakar berbahan api cecair dengan ciri-ciri rendah NOx - Ishak, Mohamad Shaiful Ashrul (2005)
A liquid fuel burner system with curved radial air swirler vane angles with swirl number variation between 0.046 to 1.911 has been investigated. A combustor with single central fuel nozzle is used to determine the effect of swirl number in emissions formation especially NOX as well as the other emissions such as CO, UHc and CO2. Swirling flow affect the formation of recirculation zone thus provides the aerodynamics blockage to stabilise the flame, improve mixing between air and fuel and affect formation of emissions. NOX reduction of more than 26% was observed as the swirl number increases from 0.046 to 1.427. In order to achieve an enhanced recirculation zone as well as to have a better control on mixing process, a swirler, which consist of an orifice plate at the outlet of radial swirler was introduced. The purpose of orifice plate insertion was to create pressure loss at the swirler outlet. The pressure loss contribute to the increase of the turbulence and hence assist in mixing of air and fuel. This technique has show a further increase in the reduction of NOX formation of about 22%. Air staged combustion has also been recognised as other solution to further reduce emissions from combustion process. The secondary air introduced downstream of the fuel rich primary zone help to complete the combustion and reduced the formation NOX by suppressing the increase in combustion temperature. This technique has also shown on improvement in the reduction of NOX emissions for about 18%.